1967
DOI: 10.1161/01.cir.35.4.631
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Studies of the Myocardium and Conduction System in Acquired Iron-Storage Disease

Abstract: SUMMARYThe myocardium, all parts of the conduction system, and the S-A node contained iron in six patients with acquired iron-storage disease. [14][15][16][17][18] A clinicopathological study was undertaken by James'9 to investigate the changes present in the myocardium and conduction system in the hearts of five patients with hemochromatosis. Two had exogenous, and three had endogenous, hemochromatosis. He found extensive iron deposits in the myocardium and in the atrioventricular (A-V) node of each heart, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 40 publications
2
24
0
1
Order By: Relevance
“…changes, frequent premature ventricular contraction is most commonly found, while sustained ventricular tachycardia is predominantly related to cardiac death (12). Iron levels in the myocardium seem to be associated more with arrhythmias and conduction disturbance than with the conduction system itself (20,21). It has been shown that patients with supraventricular arrhythmias have extensive iron deposition in the atria, and not in the sinoatrial node (20).…”
Section: Clinical Insightmentioning
confidence: 99%
See 1 more Smart Citation
“…changes, frequent premature ventricular contraction is most commonly found, while sustained ventricular tachycardia is predominantly related to cardiac death (12). Iron levels in the myocardium seem to be associated more with arrhythmias and conduction disturbance than with the conduction system itself (20,21). It has been shown that patients with supraventricular arrhythmias have extensive iron deposition in the atria, and not in the sinoatrial node (20).…”
Section: Clinical Insightmentioning
confidence: 99%
“…It tends to accumulate in myocardium (especially interventricular septum and ventricular free wall) more often than in the conduction system. Moreover, clinically, antemortem arrhythmias and conduction disturbance have shown no correlation with iron density in the conduction system (21). Other assessments, such as antioxidant levels -particularly vitamin E, which combats oxidative stress from iron toxicity -have been proposed as being indicative of iron overload cardiomyopathy in TM patients (37).…”
Section: Assessment and Markers Of Cardiac Iron Statusmentioning
confidence: 99%
“…6 Iron deposition is most common in working muscle and tends to spare the conduction system. 72,210 Postulated mechanisms for the electrophysiological effects include inhibition of fast inward sodium currents, blockage of ryanodine calcium release channel, and oxidative stress-mediated changes in sarcoplasmic calcium release and reuptake. 71,[211][212][213] Clinically, intra-atrial reentrant tachycardia and AF are the most common serious rhythm disturbances.…”
Section: Unique Electrophysiologymentioning
confidence: 99%
“…45 Early pathological examination of hearts affected by iron overload emphasized the patchiness of iron overload, 72 with evidence of atrioventricular nodal and conducting tissue having variable iron content that was not always associated with clinical evidence of arrhythmia or heart block. 210 A role of severe, untreated iron overload in the development of conduction disturbance would appear likely. The incidence of heart block has diminished drastically with effective chelation therapy in TM patients.…”
Section: Arrhythmias and Iron Loadingmentioning
confidence: 99%
“…Iron deposition in the heart cells is of outstanding interest [66][67][68]. Heart failure is the leading cause of death among hemosiderotic -thalassemia patients [69][70][71].…”
Section: Discussionmentioning
confidence: 99%